Carotid intima–media thickness in patients with cardiac syndrome X and its association with high circulating levels of asymmetric dimethylarginine - Sen, Nihat; Poyraz, Fatih; Tavil, Yusuf; Yazici, Hüseyin Ugur; Turfan, Murat; Hızal, Fatma; Topal, Salih; Erdamar, Hüsamettin; Cakir, Erdinc; Yalçın, Rıdvan; Cengel, Atiye (Atherosclerosis, 2009)
The cause of myocardial ischemia and chest pain in patients with cardiac syndrome X (CSX) has been explained by mechanisms including endothelial dysfunction. CSX patients have higher levels of asymmetric dimethylarginine (ADMA) and increased mean common carotid intima–media thickness (C-IMT). Accordingly, this study was designed to examine C-IMT with its association serum endothelial function parameters in patients with CSX. The study population consisted of 30 enrolled consecutive patients with diagnosis of CSX. As a control group, 30 individuals with the complaint of anginal chest pain without any ischemia on myocardial perfusion scintigraphy and with normal coronary angiographies were selected. C-IMT was measured by recording ultrasonographic images of both the left and the right common carotid artery. Plasma levels of l-arginine, ADMA, and nitrate/nitrite (NO x ) were measured from blood samples. Both C-IMT (mm) and carotis atherosclerotic plaques were significantly higher in patients with CSX than in control group. Also, the plasma level of NO x , l-arginine, and l-arginine/ADMA ratio were lower in patients with CSX than they were in the control group subjects. Plasma ADMA level increased in the CSX patients group. Correlation analysis showed significant positive correlation with C-IMT and plasma ADMA levels and showed significant negative correlation with plasma NO x and l-arginine levels. l-arginine/ADMA ratio and C-IMT was also showed significant negative correlation with the same analysis. CSX patients had higher plasma ADMA levels and C-IMT values than the controls, reflecting the presence of subclinical atherosclerosis. These findings suggest that, besides endothelial dysfunction, presence of atherosclerosis may also contribute to the etiopathogenesis of the CSX phenomenon.